Classification and quality of Acca sellowiana (O. Berg) Burret seeds as to tolerance to desiccation - Voss, Larissa Corradi (2020)
The objective of this paper was to determine the physiological behavior and seed quality of five genotypes of Acca sellowiana regarding desiccation. Seeds were obtained from five plants of urban backyards in the cities of Dois Vizinhos - PR (A1, A2) and Vacaria - RS (A3, A4, A5). The experiment was conducted in a bifactor arrangement (5x3), with five genotypes and three levels of water content (28%, 15% and 5%), arranged into complete randomized block design, with four replicates of 50 seeds each. Seeds were germinated on absorbent paper soaked with water, being kept in BOD chamber under temperature of 25±3°C with photoperiod of 16 hours. Germination percentage, speed index and average time were assessed by counting seeds every two days for 50 days, starting from the moment of radicle emergence. No significant differences were observed for germination percentage and all genotypes surpassing 79% of germination. Desiccation of seeds had low influence on germination speed index and average time of germination, although genotype influence was verified due to genetic variability. Genotype A5 has seeds with superior quality from the others. Acca sellowiana seeds have orthodox behavior.